Separator membrane and electrochemical device and electronic device containing the same

By using a composite isolation film in lithium-ion batteries, the transition metal ions are captured using the cation exchange layer and the conductivity is reduced, the problem of structural instability of lithium-ion batteries at high voltages is solved, and the electrochemical stability and safety are significantly improved.

CN115693028BActive Publication Date: 2025-02-14NINGDE AMPEREX TECHNOLOGY LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211259860.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-03-27
Publication Date
2025-02-14
Estimated Expiration
2039-03-27

AI Technical Summary

Technical Problem

Existing lithium-ion batteries can easily lead to unstable structure of the positive electrode active substance under high voltage, release transition metal ions, and then form lithium dendrites, which pose a risk of piercing the isolation film and affecting electrochemical stability and safety.

Method used

Using a composite isolation film, the film consists of a first porous substrate and a cation exchange layer, which captures transition metal ions through a polymer binder grafted with functional group, and reduces conductivity through a multi-layer structure design, reducing Self-discharge rate.

Benefits of technology

It effectively improves the transition metal capture rate of the electrochemical device, reduces the self-discharge rate, improves the electrochemical stability and cycling performance, and improves the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115693028B_ABST
    Figure CN115693028B_ABST
Patent Text Reader

Abstract

The present application relates to a composite isolation membrane and an electrochemical device and an electronic device including the same. Some embodiments of the present application provide a composite isolation membrane, which includes a first porous substrate and a cation exchange layer, wherein the cation exchange layer includes a second porous substrate grafted with a functional group, and the functional group is selected from the group consisting of a sulfonic acid alkali metal group, a phosphate alkali metal group and a combination thereof. The composite isolation membrane of the present application can effectively capture transition metal ions dissolved from the positive electrode plate through the cation exchange layer, thereby reducing the deposition of transition metal ions on the negative electrode plate and the self-discharge rate of the electrochemical device, so that the electrochemical stability and cycle performance of the electrochemical device are improved to a certain extent, and the safety of the electrochemical device is also significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese invention patent application with the application date of March 27, 2019, the application number of "201910237734.4", and the invention name of "Isolation membrane and electrochemical device and electronic device containing the same". Technical Field

[0002] The present application relates to the field of energy storage technology, and in particular to a composite isolation membrane and an electrochemical device and an electronic device comprising the same. Background Art

[0003] With the popularity of consumer electronic products such as laptops, mobile phones, handheld game consoles, tablets, mobile power supplies and drones, people have increasingly stringent requirements for electrochemical devices (e.g., lithium-ion batteries). For example, people not only require batteries to be lightweight, but also require them to have high capacity and long service life. Among the many batteries, lithium-ion batteries have already occupied a mainstream position in the market with their outstanding advantages such as high energy density, good safety, low self-discharge, no memory effect, and long service life. However, due to the increasing demand for high energy density of lithium-ion batteries, the operating voltage of the positive electrode active material is getting higher and higher, resulting in an unstable structure of the positive electrode active material, thereby releasing more transition metal ions at high voltage, and the transition metal ions will further form lithium dendrites on the negative electrode sheet, posing the risk of piercing the isolation membrane.

[0004] In order to improve the electrochemical stability and cycle performance of electrochemical devices, the use of composite isolation membranes is one of the feasible solutions. Therefore, in order to further improve the safety of electrochemical devices, it is necessary to further improve and design the structure and materials of the composite isolation membranes. Summary of the invention

[0005] The present application provides a composite isolation membrane and an electrochemical device and an electronic device comprising the same in an attempt to solve at least one problem existing in the related art to at least some extent.

[0006] According to the first aspect of the present application, the present application provides a composite isolation membrane, which includes: a first porous substrate and a cation exchange layer, wherein the cation exchange layer includes a second porous substrate grafted with functional groups, and the functional groups are selected from the group consisting of sulfonic acid alkali metal groups, phosphate alkali metal groups and combinations thereof.

[0007] According to some embodiments, it further includes a first coating layer including inorganic particles and a binder.

[0008] According to some embodiments, it further comprises a second coating layer comprising a polymer binder.

[0009] According to some embodiments, the polymer binder is selected from the group consisting of copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of vinylidene fluoride-trichloroethylene, polyacrylates, polyacrylic acid, polymethyl methacrylate, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene, polyhexafluoropropylene, copolymers of styrene-butadiene, and combinations thereof.

[0010] According to some embodiments, the first coating is disposed between the first porous substrate and the cation exchange layer.

[0011] According to some embodiments, the second coating layer is disposed between the first coating layer and the cation exchange layer.

[0012] According to some embodiments, the cation exchange layer is disposed between the first porous substrate and the first coating layer.

[0013] According to some embodiments, the second coating layer is disposed on the surface of the first coating layer.

[0014] According to some embodiments, the second porous substrate is selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, polyimide, ethylene-styrene copolymer, polysulfone, polyetheretherketone, polystyrene, and combinations thereof.

[0015] According to some embodiments, the grafting concentration of the functional groups is about 0.15 mmol / g to about 0.95 mmol / g.

[0016] According to some embodiments, the cation exchange layer has a thickness of about 0.5 μm to about 10 μm.

[0017] According to the second aspect of the present application, the present application provides a composite isolation membrane, which comprises: a first porous substrate and a cation exchange layer, wherein the cation exchange layer comprises a polymer binder grafted with functional groups, and the functional groups are selected from the group consisting of sulfonic acid alkali metal groups, phosphate alkali metal groups and combinations thereof.

[0018] According to some embodiments, it further includes a first coating layer, the first coating layer includes inorganic particles and a binder, and the first coating layer is disposed between the first porous substrate and the cation exchange layer.

[0019] According to some embodiments, the polymer binder is selected from the group consisting of copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of vinylidene fluoride-trichloroethylene, polyacrylates, polyacrylic acid, polymethyl methacrylate, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene, polyhexafluoropropylene, copolymers of styrene-butadiene, and combinations thereof.

[0020] According to some embodiments, the grafting concentration of the functional groups is about 0.15 mmol / g to about 0.95 mmol / g.

[0021] According to some embodiments, the cation exchange layer has a thickness of about 0.5 μm to about 10 μm.

[0022] According to the third aspect of the present application, the present application provides an electrochemical device, which includes: a positive electrode sheet, a negative electrode sheet and the composite isolation membrane in the above embodiment, wherein the composite isolation membrane is arranged between the positive electrode sheet and the negative electrode sheet.

[0023] According to a fourth aspect of the present application, the present application provides an electronic device, which includes the above-mentioned electrochemical device.

[0024] Additional aspects and advantages of the embodiments of the present application will be described, shown, or explained in part in the subsequent description through implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The following will briefly describe the drawings necessary for describing the embodiments of the present application or the prior art to facilitate the description of the embodiments of the present application. Obviously, the drawings described below are only some of the embodiments in the present application. For those skilled in the art, without the need for creative work, drawings of other embodiments can still be obtained based on the structures illustrated in these drawings.

[0026] Figure 1 It is a schematic diagram of the structure in which a composite isolation membrane of a first form is arranged in an electrode assembly according to some embodiments of the present application.

[0027] Figure 2 It is a schematic diagram of the structure in which a second type of composite isolation membrane is disposed in an electrode assembly according to some embodiments of the present application.

[0028] Figure 3 It is a schematic diagram of the structure in which a composite isolation membrane of a third form is arranged in an electrode assembly according to some embodiments of the present application.

[0029] Figure 4 This is an enlarged image of the negative electrode sheet of comparative example 1 of the present application after passing the self-discharge test under an electron microscope and an energy distribution diagram of an energy spectrometer.

[0030] Figure 5 This is an enlarged image of the negative electrode plate of Example 1 of the present application after passing the self-discharge test under an electron microscope and an energy distribution diagram of the energy spectrometer.

[0031] Figure 6 This is a diagram showing the amount of transition metal deposited on the negative electrode sheets of the lithium-ion batteries of Example 1 and Comparative Example 1 of the present application after the cycle test. DETAILED DESCRIPTION

[0032] The embodiments of the present application will be described in detail below. In the full text of the present application specification, the same or similar components and components with the same or similar functions are represented by similar reference numerals. The embodiments of the accompanying drawings described herein are illustrative, graphical, and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.

[0033] As used herein, the terms "substantially," "substantially," "essentially," and "about" are used to describe and illustrate small variations. When used in conjunction with an event or circumstance, the terms may refer to instances where the event or circumstance occurred exactly as well as instances where the event or circumstance occurred very approximately. For example, when used in conjunction with a numerical value, the terms may refer to a range of variation less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. For example, two values ​​may be considered “substantially” the same if the difference between them is less than or equal to ±10% of the average of the values ​​(e.g., less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%).

[0034] In this specification, unless otherwise specified or limited, relative terms such as "central", "longitudinal", "lateral", "front", "rear", "right", "left", "inner", "outer", "lower", "higher", "horizontal", "vertical", "above", "below", "above", "below", "top", "bottom" and their derivative terms (such as "horizontally", "downwardly", "upwardly", etc.) should be interpreted as referring to the directions described in the discussion or depicted in the drawings. These relative terms are only used for convenience of description and do not require that the present application be constructed or operated in a specific direction.

[0035] Furthermore, for ease of description, “first”, “second”, “third”, etc. may be used herein to distinguish different components in one figure or a series of figures. “First”, “second”, “third”, etc. are not intended to describe the corresponding components.

[0036] In addition, sometimes amounts, ratios and other numerical values ​​are presented in range format herein. It should be understood that such range format is for convenience and brevity, and should be flexibly understood to include not only the numerical values ​​explicitly specified as range limits, but also all individual numerical values ​​or sub-ranges encompassed within the range, as if each numerical value and sub-range were explicitly specified.

[0037] The embodiments of the present application provide a composite isolation membrane and an electrochemical device comprising the same, wherein the composite isolation membrane comprises a first porous substrate; and a cation exchange layer, wherein the cation exchange layer comprises a material layer grafted with functional groups, and the functional groups are selected from the group consisting of sulfonic acid alkali metal groups, phosphate alkali metal groups and combinations thereof. The cation exchange layer can capture transition metal ions dissolved from the positive electrode plate, and can effectively improve the transition metal capture rate in the electrochemical device; at the same time, the present application effectively reduces the conductivity of the composite isolation membrane by proposing various different forms of structural designs for the first porous substrate and the cation exchange layer, thereby reducing the self-discharge rate of the electrochemical device, thereby improving the electrochemical stability and cycle performance of the electrochemical device to a certain extent, and also significantly improving the safety of the electrochemical device.

[0038] The following will be combined Figure 1-3 This is to further illustrate the structure and material composition of the composite isolation membrane in various embodiments of the present application, as well as the configuration of the composite isolation membrane in the electrode assembly.

[0039] Figure 1 It is a schematic diagram of the structure in which a composite isolation membrane of a first form is arranged in an electrode assembly according to some embodiments of the present application.

[0040] like Figure 1 As shown, the first form of the composite isolation membrane 10 includes: a first porous substrate 11 and a cation exchange layer 12, wherein the cation exchange layer 12 includes a second porous substrate grafted with a functional group, and the functional group is selected from the group consisting of a sulfonic acid alkali metal group, a phosphate alkali metal group and a combination thereof. In addition, the composite isolation membrane 10 also includes a first coating 13 (anti-oxidation layer) and two second coatings 14 (bonding layers), the first coating 13 includes inorganic particles and a binder, and the second coating 14 includes a polymer binder. The first coating 13 is disposed between the first porous substrate 11 and the cation exchange layer 12, and the second coating 14 is respectively disposed between the first coating 13 and the cation exchange layer 12 and on the other side surface of the first porous substrate 11 relative to the cation exchange layer.

[0041] In other embodiments, the first coating layer 13 may also be disposed on the other side of the first porous substrate 11 relative to the cation exchange layer 12, for example, between the first porous substrate 11 and the second coating layer 14, or on the surface of the second coating layer 14 facing the negative electrode plate 16. In other embodiments, the composite separator 10 may also include more than two first coating layers 13, wherein at least one first coating layer 13 is disposed on the first porous substrate 11. Figure 1 In the position shown, at least another first coating layer 13 is disposed between the first porous substrate 11 and the second coating layer 14 , or is disposed on the surface of the second coating layer 14 facing the negative electrode sheet 16 .

[0042] Figure 2 It is a schematic diagram of the structure in which a second type of composite isolation membrane is disposed in an electrode assembly according to some embodiments of the present application.

[0043] like Figure 2 As shown, the second form of the composite isolation membrane 20 includes a first porous substrate 21 and a cation exchange layer 22, wherein the cation exchange layer 22 includes a second porous substrate grafted with a functional group, and the functional group is selected from the group consisting of a sulfonic acid alkali metal group, a phosphate alkali metal group and a combination thereof. In addition, the composite isolation membrane 10 also includes a first coating 23 (anti-oxidation layer) and two second coatings 24 (bonding layers), the first coating 23 includes inorganic particles and a binder, and the second coating 24 includes a polymer binder. Compared with the first form of the composite isolation membrane 10, the cation exchange layer 22 of the composite isolation membrane 20 is arranged between the first porous substrate 21 and the first coating 23, wherein the second coating 24 is respectively arranged on the other side surface of the first coating 23 relative to the cation exchange layer 22 and the other side surface of the first porous substrate 21 relative to the cation exchange layer.

[0044] In other embodiments, the first coating layer 23 may also be disposed on the other side of the first porous substrate 21 relative to the cation exchange layer, for example, between the first porous substrate 21 and the second coating layer 24, or on the surface of the second coating layer 24 facing the negative electrode plate 16. In other embodiments, the composite separator 20 may also include more than two first coating layers 23, wherein at least one first coating layer 23 is disposed on the first porous substrate 21. Figure 2 In the position shown, at least another first coating layer 23 is disposed between the first porous substrate 21 and the second coating layer 24 , or is disposed on the surface of the second coating layer 24 facing the negative electrode sheet 16 .

[0045] Figure 3It is a schematic diagram of the structure in which a third type of isolation membrane is disposed in an electrode assembly according to some embodiments of the present application.

[0046] like Figure 3 As shown, the third form of the composite isolation membrane 30 includes a first porous substrate 31 and a cation exchange layer 32, wherein the cation exchange layer 32 includes a polymer binder grafted with a functional group, and the functional group is selected from the group consisting of a sulfonic acid alkali metal group, a phosphate alkali metal group and a combination thereof. In addition, the composite isolation membrane 30 also includes a first coating 33 (anti-oxidation layer) and a second coating 34 (bonding layer), the first coating 33 includes inorganic particles and a binder, and the second coating 34 includes a polymer binder. Similar to the first form of the composite isolation membrane 10, the first coating 33 of the composite isolation membrane 30 is arranged between the first porous substrate 31 and the cation exchange layer 32, and the second coating 34 is arranged on the other side surface of the first porous substrate 31 relative to the cation exchange layer 32.

[0047] In other embodiments, the first coating layer 33 may be further disposed on the other side of the first porous substrate 31 relative to the cation exchange layer 32, for example, between the first porous substrate 31 and the second coating layer 34, or on the surface of the second coating layer 34 facing the negative electrode plate 16. In other embodiments, the composite separator 30 may also include more than two first coating layers 33, wherein at least one first coating layer 33 is disposed on the first porous substrate 31. Figure 3 In the position shown, at least another first coating 33 is disposed between the first porous substrate 31 and the second coating 34 , or is disposed on the surface of the second coating 34 facing the negative electrode sheet 16 .

[0048] In some embodiments, those skilled in the art may also choose whether to set or remove the second coating (14, 24, 34) in the composite isolation film (10, 20, 30) according to specific needs, without being restricted by Figure 1-3 restrictions.

[0049] In some embodiments, Figure 1-3 As shown, the cation exchange layer (12, 22, 32) in the composite isolation membrane (10, 20, 30) is arranged on a side close to the positive electrode plate 15. The transition metal ions dissolved from the positive electrode plate 15 are captured by the cation exchange layer (12, 22, 32), thereby effectively improving the capture rate of transition metal ions in the electrochemical device, and avoiding the transition metal ions from being deposited on the negative electrode to form dendrites after passing through the isolation membrane, which may cause safety risks.

[0050] In some embodiments, the first porous substrate ( 11 , 21 , 31 ) has a thickness of about 1 μm to about 20 μm.

[0051] In some embodiments, the cation exchange layer (12, 22, 32) has a thickness of about 0.5 μm to about 10 μm.

[0052] In some embodiments, the first coating (13, 23, 33) has a thickness of about 0.5 μm to about 10 μm.

[0053] In some embodiments, the second coating (14, 24, 34) has a thickness of about 0.5 μm to about 10 μm.

[0054] In the above embodiments, the functional groups in the cation exchange layers (12, 22 and 32) include at least one of a sulfonic acid alkali metal group and a phosphate alkali metal group, wherein the sulfonic acid alkali metal group includes at least one of a lithium sulfonate group (-SO3Li), a sodium sulfonate group (-SO3Na) and a potassium sulfonate group (-SO3K), and the phosphate alkali metal includes at least one of a lithium phosphate group (-PO3Li2), a sodium phosphate group (-PO3Na2) and a potassium phosphate group (-PO3K2). In some embodiments, the sulfonic acid alkali metal group is a lithium sulfonate group, and the phosphate alkali metal group is a lithium phosphate group.

[0055] In some embodiments, the cations in the functional groups grafted to the cation exchange layers (12, 22 and 32) may be lithium ions. When the lithium ions are replaced by transition metal ions, they may become a lithium source in the electrolyte, further improving the cycle capacity of the electrochemical device.

[0056] In the above embodiments, the material layer (second porous substrate or polymer binder) grafted with functional groups in the cation exchange layer (12, 22 and 32) can determine the degree of grafting of functional groups on the material layer and its exchange capacity for transition metal ions by measuring the grafting concentration of the functional groups, wherein the grafting concentration of the functional groups refers to the ratio of the molar number of the functional groups to the mass of the cation exchange layer.

[0057] In some embodiments, the grafted concentration of the functional group can be measured by an acid-base titration method, and the steps are as follows: first, a certain mass of the cation exchange layer (not yet neutralized with the alkali metal ions, only grafted with the sulfonic acid group (-SO3H) or the phosphate group (-PO3H2)), then the cation exchange layer is dissolved in water, phenolphthalein is used as an indicator, and titrated with a sodium hydroxide (NaOH) solution to obtain the molar number of the consumed sodium hydroxide solution.

[0058] In some embodiments, when the functional group used is a sulfonic acid group, the grafting concentration A of the functional group (sulfonic acid group) in the cation exchange layer can be calculated by the following formula:

[0059] Grafting concentration A (mmol / g) = (V × N / m),

[0060] Wherein, V is the titrated volume of the sodium hydroxide (L), N is the volume molar concentration of the sodium hydroxide solution (mmol / L), and m is the mass of the cation exchange layer (g).

[0061] In some embodiments, when the functional group used is a phosphate group, the grafting concentration A of the functional group (phosphate group) in the cation exchange layer can be calculated by the following formula:

[0062] Grafting concentration A (mmol / g) = (V×N / (2×m)),

[0063] Wherein, V is the titrated volume of the sodium hydroxide (L), N is the volume molar concentration of the sodium hydroxide solution (mmol / L), and m is the mass of the cation exchange layer (g).

[0064] In some embodiments, the material layer (second porous substrate or polymer binder) grafted with functional groups in the cation exchange layer (12, 22 and 32) has a grafting concentration of about 0.15 mmol / g to about 0.95 mmol / g. In some embodiments, the grafting concentration of the functional groups can also be tested by other methods.

[0065] In some embodiments, the inorganic particles described in the above embodiments can be selected from the group consisting of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, barium sulfate and combinations thereof.

[0066] In some embodiments, the binder described in the above embodiments can be selected from the group consisting of copolymers of vinylidene fluoride and hexafluoropropylene, copolymers of vinylidene fluoride and trichloroethylene, polyacrylates, polyacrylic acids, polyacrylates, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, copolymers of acrylonitrile-styrene-butadiene, polyvinyl alcohol, polyvinyl ether, polytetrafluoroethylene, polyhexafluoropropylene, copolymers of styrene-butadiene, polyvinylidene fluoride and combinations thereof.

[0067] In some embodiments, the polymer binder described in the above embodiments can be selected from the group consisting of copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of vinylidene fluoride-trichloroethylene, polyacrylates, polyacrylic acid, polymethyl methacrylate, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene, polyhexafluoropropylene, copolymers of styrene-butadiene and combinations thereof. The polymer binder can be in the form of particles, fibers, meshes, or other forms, has strong bonding force, and can well bond the electrode in contact with it.

[0068] In some embodiments, the first porous substrate in the above embodiments is a polymer film, a multilayer polymer film, or a non-woven fabric formed by any one polymer or a mixture of two or more selected from the following: polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyphenylene phthalamide, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene ether, cyclic olefin copolymer, polyphenylene sulfide and polyethylene naphthalene.

[0069] In some embodiments, the second porous substrate described in the above embodiments is selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, polyimide, ethylene-styrene copolymer, polysulfone, polyetheretherketone, polystyrene and combinations thereof. The second porous substrate can isolate electrons and conduct lithium ions, but it has no adhesiveness.

[0070] In some embodiments, the method for preparing the first type of composite isolation membrane comprises the following steps:

[0071] The inorganic particles are mixed with the binder and dissolved in a dilute solvent to form a first coating slurry (anti-oxidation layer), and then the first coating slurry is uniformly coated on one or both sides of the first porous substrate by a micro-concave coating method, and then dried to obtain a double-layer or triple-layer structure of the first coating and the first porous substrate; the polymer binder and the auxiliary binder are mixed and dissolved in a dilute solvent to form a second coating slurry (bonding layer), and then the second coating slurry is uniformly coated on one or both sides of the double-layer or triple-layer structure by a micro-concave coating method, and then dried to obtain the first porous substrate, the first coating and the second coating having a multi-layer composite structure.

[0072] The second porous substrate material is dissolved in a non-aqueous solvent, and at least one of a vulcanizing agent and a phosphating agent is added, wherein the ratio of the at least one of the vulcanizing agent and the phosphating agent to the second porous substrate material is 1 mL / g to about 50 mL / g, and the second porous substrate material is functionalized at a temperature of 20°C to 100°C for about 0.5h to 20h; lithium hydroxide solution is added, the temperature is adjusted to about 45°C, the sediment is taken out after stirring and dried to obtain a second porous substrate material grafted with functional groups; then the second porous substrate material is dissolved in a dilute solvent with a binder to form a cation exchange layer slurry, and then the cation exchange layer slurry is evenly coated on one side of the multilayer composite structure close to the first coating layer by a micro-concave coating method, and after drying and cutting, the first form of the composite isolation membrane is obtained.

[0073] In some embodiments, the method for preparing the second type of composite isolation membrane comprises the following steps:

[0074] The second porous substrate material is dissolved in a non-aqueous solvent, and at least one of a sulfiding agent and a phosphating agent is added, wherein the ratio of the at least one of the sulfiding agent and the phosphating agent to the second porous substrate material is 1 mL / g to about 50 mL / g, and the second porous substrate material is functionalized at a temperature of 20°C to 100°C for about 0.5h to 20h; lithium hydroxide solution is added, the temperature is adjusted to about 45°C, the sediment is taken out after stirring and dried to obtain the second porous substrate material grafted with functional groups; then the second porous substrate material grafted with functional groups and a binder are dissolved in a dilute solvent to form a cation exchange layer slurry, and then the cation exchange layer slurry is uniformly coated on one side of the first porous substrate by a micro-concave coating method, and dried to obtain a double-layer structure of the cation exchange layer and the first porous substrate.

[0075] The inorganic particles are mixed with the binder and dissolved in a dilute solvent to form a first coating slurry (anti-oxidation layer), and the first coating slurry is evenly coated on one side surface of the cation exchange layer in the double-layer structure or on both sides of the double-layer structure by a micro-concave coating method, and dried to obtain a composite structure of the first coating and the double-layer structure; then the polymer binder and the auxiliary binder are mixed and dissolved in a dilute solvent to form a second coating slurry (bonding layer), and the second coating slurry is evenly coated on one side or both sides of the composite structure by a micro-concave coating method, and after drying and cutting, the second form of the composite isolation membrane is obtained.

[0076] In some embodiments, the method for preparing the third type of composite isolation membrane comprises the following steps:

[0077] The inorganic particles and the binder are mixed and dissolved in a dilute solvent to form a first coating slurry (antioxidant layer), and then the first coating slurry is uniformly coated on one or both surfaces of the first porous substrate by a micro-concave coating method, and dried to obtain a double-layer or triple-layer structure of the first coating and the first porous substrate;

[0078] A polymer binder is dissolved in a non-aqueous solvent, and at least one of a vulcanizing agent and a phosphating agent is added, wherein the ratio of at least one of the vulcanizing agent and the phosphating agent to the second porous substrate material is 1 mL / g to about 50 mL / g, and the material is functionalized at a temperature of 20°C to 100°C for about 0.5h to 20h; a lithium hydroxide solution is added, the temperature is adjusted to about 45°C, the sediment is taken out after stirring and dried to obtain a polymer binder material grafted with functional groups, which is then dissolved in a dilute solvent with an auxiliary binder to form a cation exchange layer slurry, and then the cation exchange layer slurry is evenly coated on one side of the double-layer or triple-layer structure close to the first coating layer by a micro-concave coating method; then the polymer binder and the auxiliary binder are mixed and dissolved in a dilute solvent to form a second coating slurry (bonding layer), and the second coating slurry is evenly coated on one or both sides of the composite structure by a micro-concave coating method, and after drying and cutting, the third form of the composite isolation membrane is obtained.

[0079] The preparation method of the composite isolation membrane in the embodiment of the present application can be a conventional method in the art, but is not limited thereto.

[0080] Some embodiments of the present application also provide an electrochemical device including the composite separator of the present application. In some embodiments, the electrochemical device is a lithium-ion battery. The lithium-ion battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a composite separator according to the present application, wherein the composite separator is disposed between the positive electrode sheet and the negative electrode sheet. The cation exchange layer improves the wetting and liquid retention capabilities of the electrode assembly in the electrochemical device, thereby improving the electrochemical stability and cycle performance of the electrochemical device.

[0081] In the above-mentioned lithium-ion battery, the positive electrode plate includes a positive electrode material capable of absorbing and releasing lithium (Li) (hereinafter, sometimes referred to as "positive electrode material capable of absorbing / releasing lithium Li"). Examples of positive electrode materials capable of absorbing / releasing lithium (Li) may include one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium iron phosphate, lithium titanate, and lithium-rich manganese-based materials.

[0082] The negative electrode sheet includes a negative electrode material capable of absorbing and releasing lithium (Li) (hereinafter, sometimes referred to as "a negative electrode material capable of absorbing / releasing lithium Li"). Examples of negative electrode materials capable of absorbing / releasing lithium (Li) may include carbon materials, metal compounds, oxides, sulfides, lithium nitrides such as LiN3, lithium metal, metals that form alloys with lithium, and polymer materials.

[0083] The lithium-ion battery of the present application further comprises an electrolyte, which may be one or more of a gel electrolyte, a solid electrolyte and an electrolyte, wherein the electrolyte comprises a lithium salt and a non-aqueous solvent.

[0084] In some embodiments, the lithium salt is selected from one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB and lithium difluoroborate. For example, the lithium salt is selected from LiPF6 because it can provide high ionic conductivity and improve cycle characteristics.

[0085] The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof.

[0086] The carbonate compound may be a linear carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.

[0087] Examples of the above other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphoric acid esters and combinations thereof.

[0088] In some embodiments, the preparation method of the lithium-ion battery includes: winding or stacking the positive electrode plate in the above embodiment, the isolation membrane of the present application and the negative electrode plate in sequence into an electrode assembly, placing the electrode assembly in, for example, an aluminum-plastic film, and injecting an electrolyte, followed by vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.

[0089] It will be understood by those skilled in the art that, although lithium-ion batteries are used as examples above, after reading this application, it will be appreciated by those skilled in the art that the composite separator of the present application can be used in other suitable electrochemical devices. Such an electrochemical device includes any device in which an electrochemical reaction occurs, and its specific examples include all kinds of primary batteries, secondary batteries, fuel cells, solar cells or capacitors. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.

[0090] Some embodiments of the present application further provide an electronic device, which includes the electrochemical device in the embodiments of the present application.

[0091] The electronic device of the embodiment of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc. Specific embodiments

[0093] Some specific embodiments and comparative examples are listed below, and their electrochemical devices (lithium-ion batteries) are subjected to transition metal capture rate tests, self-discharge tests, nail penetration tests, and cycle performance tests to better illustrate the technical solutions of the present application.

[0094] Preparation of positive electrode

[0095] Aluminum foil is used as the positive electrode current collector, and a layer of lithium cobalt oxide slurry (positive electrode material layer) is uniformly coated on the surface of the positive electrode current collector. The composition of the lithium cobalt oxide slurry is 94wt% lithium cobalt oxide, 3wt% polyvinylidene fluoride and 3wt% acetylene black. The positive electrode current collector coated with the lithium cobalt oxide slurry is then baked at 120°C for 1h, and then cold pressed, cut and slit to prepare the positive electrode sheet.

[0096] Preparation of negative electrode

[0097] Copper foil is used as the negative electrode current collector, and a layer of graphite slurry (negative electrode material layer) is evenly coated on the surface of the negative electrode current collector. The composition of the graphite slurry is 95wt% artificial graphite, 2wt% acetylene black, 2wt% styrene-butadiene rubber and 1wt% sodium carboxymethyl cellulose. The negative electrode current collector coated with the graphite slurry is then baked at 120°C for 1h, and then cold pressed, cut and slit to prepare a negative electrode sheet.

[0098] Preparation of electrolyte

[0099] In an environment where the water content is less than 10 ppm, lithium hexafluorophosphate and a non-aqueous organic solvent (ethylene carbonate (EC): propylene carbonate (PC): diethyl carbonate (DEC) = 1:1:1, mass ratio) are prepared at a mass ratio of 8:92 to form an electrolyte.

[0100] Preparation of lithium-ion batteries

[0101] The composite isolation membranes in the embodiments and comparative examples are prepared into lithium-ion batteries using the following preparation method. Specifically, the composite isolation membranes prepared in the following embodiments and comparative examples are stacked in order according to the above-mentioned positive electrode sheet, the composite isolation membrane and the above-mentioned negative electrode sheet, wherein the side of each composite isolation membrane having a cation exchange layer faces the positive electrode sheet, and the side farther from the cation exchange layer faces the negative electrode sheet, so that the isolation membrane is located between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound into an electrode assembly. The electrode assembly is then placed in an aluminum foil packaging bag, and after dehydration at 80°C, a dry electrode assembly is obtained. The above-mentioned electrolyte is then injected into the dry electrode assembly, and after vacuum packaging, standing, formation, shaping and other processes, the preparation of the lithium-ion batteries of the following embodiments and comparative examples is completed.

[0102] Example 1

[0103] Alumina and polyacrylate are mixed in a mass ratio of 90:10 and dissolved in deionized water to form a first coating slurry (antioxidant layer), and the solid content of the first coating slurry is 45%. The first coating slurry is then uniformly coated on one side of a polyethylene porous substrate with a thickness of 7 μm by a micro-concave coating method, and dried to obtain a double-layer structure of the first coating and the polyethylene substrate, wherein the thickness of the first coating is 2 μm. Polyvinylidene fluoride and polyacrylate are mixed in a mass ratio of 3:2 and dissolved in deionized water to form a second coating slurry (adhesive layer), and the solid content of the second coating slurry is 30%. The second coating slurry is then uniformly coated on both sides of the double-layer structure of the first coating and the polyethylene porous substrate by a micro-concave coating method, and dried to obtain the first porous substrate, the first coating and the second coating having a multi-layer composite structure, wherein the single-side thickness of the second coating is 1 μm.

[0104] The polyethylene particles are dissolved in 1,2-dichloroethane to form a solution with a solid content of 30%, and concentrated sulfuric acid is added to the solution, wherein the ratio of concentrated sulfuric acid to polyethylene particles is 3.0 mL / g, and the solution is functionalized at a temperature of 60°C for 4 hours. A lithium hydroxide solution with a concentration of 2 mol / L is added so that the molar ratio of lithium hydroxide to concentrated sulfuric acid is 2.4:1, and then the temperature is adjusted to about 45°C. After stirring for 1 hour, the sediment is taken out and dried to obtain a polyethylene material grafted with a functional group. The polyethylene material grafted with a functional group is mixed with polyacrylate in a mass ratio of 3:2 and dissolved in deionized water to form a cation exchange layer slurry, wherein the solid content of the cation exchange layer slurry is 30%. Subsequently, the cation exchange layer slurry is uniformly coated on one side of the multilayer composite structure close to the first coating layer by a micro-concave coating method to form a cation exchange layer, wherein the thickness of the cation exchange layer is 3 μm, and after drying and cutting, the first form of composite isolation membrane is obtained.

[0105] Example 2

[0106] The polyethylene particles are dissolved in 1,2-dichloroethane to form a solution with a solid content of 30%, and concentrated sulfuric acid is added to the solution, wherein the ratio of concentrated sulfuric acid to polyethylene particles is 3.0 mL / g, and the solution is functionalized at a temperature of 60°C for 4 hours. A lithium hydroxide solution with a concentration of 2 mol / L is added so that the molar ratio of lithium hydroxide to concentrated sulfuric acid is 2.4:1, and then the temperature is adjusted to about 45°C. After stirring for 1 hour, the sediment is taken out and dried to obtain a polyethylene material grafted with functional groups. The polyethylene material grafted with functional groups is mixed with polyacrylate in a mass ratio of 3:2 and dissolved in deionized water to form a cation exchange layer slurry, and the solid content of the cation exchange layer slurry is 30%. Subsequently, the cation exchange layer slurry is uniformly coated on one side of a polyethylene porous substrate with a thickness of 7 μm by a micro-concave coating method, wherein the thickness of the cation exchange layer is 3 μm, and a double-layer structure of the cation exchange layer and the polyethylene porous substrate is obtained after drying;

[0107] Alumina and polyacrylate are mixed in a mass ratio of 90:10 and dissolved in deionized water to form a first coating slurry (antioxidant layer), and the solid content of the first coating slurry is 45%. The first coating slurry is evenly coated on one side of the cation exchange layer in the double-layer structure by a micro-concave coating method, and a composite structure of the first coating and the double-layer structure is obtained after drying, wherein the thickness of the first coating is 2μm. Polyvinylidene fluoride and polyacrylate are mixed in a mass ratio of 3:2 and dissolved in deionized water to form a second coating slurry (bonding layer), and the solid content of the second coating slurry is 30%. Subsequently, the second coating slurry is evenly coated on both sides of the composite structure by a micro-concave coating method, wherein the single-sided thickness of the second coating is 1μm, and after drying and cutting, the second form of the composite isolation membrane is obtained.

[0108] Example 3

[0109] Alumina and polyacrylate were mixed in a mass ratio of 90:10 and dissolved in deionized water to form a first coating slurry (antioxidant layer), wherein the solid content of the first coating slurry was 45%. The first coating slurry was uniformly coated on one side of a polyethylene porous substrate having a thickness of 7 μm by a micro-concave coating method, and dried to obtain a double-layer structure of the first coating and the polyethylene porous substrate, wherein the thickness of the first coating was 2 μm.

[0110] Then, polyvinylidene fluoride is dissolved in 1,2-dichloroethane to form a solution with a solid content of 30%, and concentrated sulfuric acid is added to the solution, wherein the ratio of concentrated sulfuric acid to polyvinylidene fluoride is 3.0 mL / g, and it is functionalized at a temperature of 60°C for 4 hours. A lithium hydroxide solution with a concentration of 2 mol / L is added so that the molar ratio of lithium hydroxide to concentrated sulfuric acid is 2.4:1, and then the temperature is adjusted to about 45°C. After stirring for 1 hour, the sediment is taken out and dried to obtain a polyvinylidene fluoride material grafted with a functional group. The polyvinylidene fluoride material grafted with a functional group is mixed with a polyacrylate in a mass ratio of 3:2 and dissolved in deionized water to form a polymer binder slurry (bonding layer) grafted with a functional group, and the solid content of the polymer binder slurry grafted with a functional group is 30%. Subsequently, the polymer binder slurry grafted with functional groups is evenly coated on one side of the first coating in the double-layer structure of the first coating and the polyethylene substrate by a micro-concave coating method to form a cation exchange layer, and the second coating slurry same as that described in Examples 1 and 2 is coated on the other side of the double-layer structure to form a second coating, wherein the thickness of the cation exchange layer is 3 μm and the thickness of the second coating is 1 μm. After drying and cutting, the third form of the composite isolation membrane is obtained.

[0111] Example 4

[0112] The preparation method is the same as that of Example 3, except that in Example 4, concentrated phosphoric acid (H2PO3) is added to the polyvinylidene fluoride and 1,2-dichloroethane solution, wherein the ratio of concentrated phosphoric acid to polyvinylidene fluoride is 3.0 mL / g; and the solution is functionalized at a temperature of 60°C for 4 hours; and then a lithium hydroxide solution with a concentration of 2 mol / L is added, so that the molar ratio of lithium hydroxide to concentrated phosphoric acid is 2.4:1.

[0113] Example 5

[0114] The preparation method is the same as that of Example 3, except that the thickness of the cation exchange layer in Example 5 is 1 μm.

[0115] Example 6

[0116] The preparation method is the same as that of Example 3, except that the thickness of the cation exchange layer in Example 6 is 5 μm.

[0117] Example 7

[0118] The preparation method is the same as that of Example 3, except that the thickness of the cation exchange layer in Example 7 is 8 μm.

[0119] Example 8

[0120] The preparation method is the same as that of Example 3, except that the ratio of concentrated sulfuric acid to polyvinylidene fluoride in Example 8 is 1.0 mL / g.

[0121] Example 9

[0122] The preparation method is the same as that of Example 3, except that the ratio of concentrated sulfuric acid to polyvinylidene fluoride in Example 9 is 5.0 mL / g.

[0123] Example 10

[0124] The preparation method is the same as that of Example 3, except that the ratio of concentrated sulfuric acid to polyvinylidene fluoride in Example 10 is 8.0 mL / g.

[0125] Embodiment 11

[0126] The preparation method is the same as that of Example 3, except that in Example 11, the functionalization is carried out at a temperature of 20° C. for 4 hours.

[0127] Example 12

[0128] The preparation method is the same as that of Example 3, except that in Example 12, the functionalization is carried out at a temperature of 40° C. for 4 hours.

[0129] Example 13

[0130] The preparation method is the same as that of Example 3, except that in Example 13, the functionalization is carried out at a temperature of 80° C. for 4 hours.

[0131] Embodiment 14

[0132] The preparation method is the same as that of Example 3, except that in Example 14, the functionalization is carried out at a temperature of 60° C. for 2 h.

[0133] Embodiment 15

[0134] The preparation method is the same as that of Example 3, except that in Example 15, the functionalization is carried out at a temperature of 60°C for 6 hours.

[0135] Example 16

[0136] The preparation method is the same as that of Example 1, except that in Example 16, the functionalization is carried out at a temperature of 60° C. for 8 h.

[0137] Embodiment 17

[0138] The preparation method is the same as that of Example 3, except that the thickness of the cation exchange layer in Example 17 is 0.5 μm.

[0139] Embodiment 18

[0140] The preparation method is the same as that of Example 3, except that the thickness of the cation exchange layer in Example 18 is 15 μm.

[0141] Embodiment 19

[0142] The preparation method is the same as that of Example 3, except that the ratio of concentrated sulfuric acid to polyvinylidene fluoride in Example 19 is 0.5 mL / g.

[0143] Comparative Example 1

[0144] Alumina and polyacrylate are mixed in a mass ratio of 90:10 and dissolved in deionized water to form a first coating slurry (antioxidant layer), and the solid content of the first coating slurry is 45%. The first coating slurry is then uniformly coated on one side of a polyethylene porous substrate with a thickness of 7 μm by a micro-concave coating method, and dried to obtain a double-layer structure of the first coating and the polyethylene substrate, wherein the thickness of the first coating is 2 μm. Polyvinylidene fluoride and polyacrylate are mixed in a mass ratio of 3:2 and dissolved in deionized water to form a second coating slurry (adhesive layer), and the solid content of the second coating slurry is 30%. The second coating slurry is then uniformly coated on both surfaces of the double-layer structure of the first coating and the polyethylene-based porous material by a micro-concave coating method, and dried to obtain the first porous substrate, the first coating and the second coating having a multi-layer composite structure, wherein the single-side thickness of the second coating is 1 μm.

[0145] The grafting concentration of the composite isolation membranes of the above embodiments and comparative examples was measured. After the lithium-ion battery was manufactured, its capacity, thickness, width, and length were recorded to determine the volume energy density of the lithium-ion battery. The lithium-ion battery was then subjected to cycle performance test, metal capture rate test, self-discharge test, and nail penetration test.

[0146] Cyclic performance test

[0147] The lithium-ion batteries of the following examples and comparative examples are placed in a thermostat at 25°C ± 2°C, charged to 4.4V at 0.7C constant current, then charged to 0.05C at 4.4V constant voltage, and finally discharged to 3.0V at 0.5C constant current. This is a charge and discharge cycle process, and the discharge capacity of the lithium-ion battery in the first cycle is recorded; then 300 charge and discharge cycles are performed according to the above method, and the discharge capacity of the lithium-ion battery in the 300th cycle is recorded. Take 5 lithium-ion batteries in each group and calculate the average value of the capacity retention rate of the lithium-ion battery. Capacity retention rate of lithium-ion battery = discharge capacity of the 300th cycle (mAh) / discharge capacity after the first cycle (mAh) × 100%.

[0148] Transition metal capture rate test

[0149] The transition metal capture rate is defined as follows:

[0150] Transition metal capture rate γ = 1-(negative electrode transition metal deposition amount / positive electrode transition metal loss amount)

[0151] The amount of transition metal deposition on the negative electrode sheet and the amount of transition metal loss on the positive electrode sheet of the lithium-ion battery are obtained by an inductively coupled plasma spectrometer (ICP). The specific steps are as follows:

[0152] The uncycled lithium-ion battery is discharged to 2.5V to 3.0V, and then disassembled to remove the negative electrode sheet and the positive electrode sheet, and the removed negative electrode sheet and the positive electrode sheet are soaked in dimethyl carbonate for 2 hours, and the negative electrode sheet and the positive electrode sheet are naturally dried after soaking; the negative electrode sheet and the positive electrode sheet are respectively placed in 1540.25mm 2 The sample was punched out from a mold, and then an inductively coupled plasma spectrometer was used to obtain the amount of transition metal deposition on the negative electrode sheet of the uncycled lithium-ion battery and the amount of transition metal loss on the positive electrode sheet of the uncycled lithium-ion battery.

[0153] The lithium-ion battery after 300 cycles of testing was discharged to 2.5V to 3.0V, and then disassembled to remove the negative electrode sheet and the positive electrode sheet, and the removed negative electrode sheet and the positive electrode sheet were soaked in dimethyl carbonate for 2 hours, and the negative electrode sheet and the positive electrode sheet were naturally dried after soaking; the negative electrode sheet and the positive electrode sheet were placed in a 1540.25mm 2 The samples were punched out from a mold, and then an inductively coupled plasma spectrometer was used to obtain the amount of transition metal deposition on the negative electrode sheet of the lithium-ion battery after 300 cycle tests and the amount of transition metal loss on the positive electrode sheet of the lithium-ion battery after 300 cycle tests.

[0154] Five lithium-ion batteries are taken from each of the two groups, and the average values ​​of the transition metal deposition amount of the negative electrode sheet and the transition metal loss amount of the positive electrode sheet of the lithium-ion batteries are calculated, wherein the transition metal deposition amount of the negative electrode sheet is the transition metal deposition amount of the negative electrode sheet of the lithium-ion battery after 300 cycles of testing minus the transition metal deposition amount of the negative electrode sheet of the lithium-ion battery that has not been cycled, and the positive electrode sheet metal loss amount is the transition metal loss amount of the positive electrode sheet of the lithium-ion battery that has not been cycled minus the transition metal loss amount of the positive electrode sheet of the lithium-ion battery after 300 cycles of testing.

[0155] Self-discharge test

[0156] The lithium-ion battery was placed in a constant temperature box at 25°C, charged to 4.4V at a constant current of 0.5C, and then charged to 0.05C at a constant voltage, and the initial voltage V1 of the lithium-ion battery was recorded; the lithium-ion battery was then placed at a constant voltage of 45°C for 1000h, and the final voltage V2 of the lithium-ion battery was tested, and the self-discharge rate value was obtained according to the following formula:

[0157] Self-discharge rate k(mV / h)=(V1-V2) / 1000(h),

[0158] Nail penetration test

[0159] Place the lithium-ion battery in a 25℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at a constant current of 0.5C to a voltage of 4.4V, and then charge it at a constant voltage of 4.4V to a current of 0.025C. Transfer the fully charged lithium-ion battery to the nail penetration tester, maintain the test environment temperature at 25℃±2℃, and use a steel nail with a diameter of 4mm to uniformly penetrate the center of the lithium-ion battery at a speed of 30mm / s. Keep it for 300 seconds. The lithium-ion battery is considered to have passed if it does not smoke, catch fire, or explode. Test 10 lithium-ion batteries each time, and use the number of lithium-ion batteries that pass the nail penetration test as an indicator for evaluating the safety performance of lithium-ion batteries.

[0160] The specific implementation parameters of the above Examples 1-19 and Comparative Example 1 and their grafting concentration results are shown in Table 1 below.

[0161] Table 1

[0162]

[0163] The electrochemical devices of the above-mentioned Examples 1-19 and Comparative Example 1 were tested for transition metal capture rate, self-discharge, nail penetration and cycle performance, and the results are shown in Table 2 below.

[0164] Table 2

[0165]

[0166] It can be seen from Table 2 that, compared with Comparative Example 1, the electrochemical device with a composite isolation membrane in the embodiment of the present application has significant improvements in both safety performance and cycle performance. Specifically, by comparing Comparative Example 1 with Examples 1-19, it can be seen that the electrochemical device with a composite isolation membrane in the embodiment of the present application can effectively improve its transition metal capture rate and reduce the self-discharge rate in the transition metal capture rate test and the self-discharge test. This represents that the composite isolation membrane of the present application can effectively capture transition metal ions and has a lower electrical conductivity, thereby improving the self-discharge rate of the electrochemical device. In addition, compared with Comparative Example 1, the electrochemical devices with a composite isolation membrane in Examples 1-19 of the present application also show relatively excellent results in the nail penetration test or the cycle performance test, effectively improving the safety performance and cycle performance of the electrochemical device.

[0167] It can be seen from Table 1 and Table 2 that the composite isolation membranes of the first form, the second form and the third form provided in Examples 1-3 of the present application can achieve a nail penetration success rate of 10 / 10, a self-discharge rate of less than 0.04 and a capacity retention rate of more than 93.2%.

[0168] The electrochemical device of Example 4 of the present application also showed an excellent nail penetration success rate, a self-discharge rate of 0.05, and a capacity retention rate of 92.2%. It can be seen that the cation exchange layer using lithium phosphate as a functional group can also improve the transition metal ion deposition of its electrochemical device, thereby improving its safety performance and cycle performance.

[0169] Comparison of Examples 5-7, 17 and 18 shows that when the thickness of the cation exchange layer in the composite isolation membrane of the present application is in the range of 0.5 μm to 10 μm, the electrochemical device can maintain a relatively excellent safety performance and cycle performance.

[0170] Depending on the different specific implementation parameters in the manufacturing process, the grafting concentration of the functional groups on the cation exchange layer in the composite isolation membrane of the present application will be affected by the ratio of the sulfur / phosphating agent to the substrate, the operating temperature of the sulfur / phosphating process, and the operating time of the sulfur / phosphating process, thereby affecting the cation exchange layer's ability to capture transition metal ions.

[0171] By comparing Examples 8-10 and 19, it can be seen that when the ratio of the sulfur / phosphating agent to the substrate is within the range of the embodiments of the present application, the grafting concentration of the functional groups on the cation exchange layer can be maintained at a certain value to maintain its ability to capture transition metal ions, thereby improving the transition metal capture rate of the electrochemical device.

[0172] Similarly, by comparing Examples 11-16, it can be seen that when the time or reaction temperature in the functionalization process is within the range of the embodiments of the present application, the grafted concentration of the functional groups on the cation exchange layer can be maintained at a certain value to maintain its ability to capture transition metal ions, thereby improving the transition metal capture rate of the electrochemical device.

[0173] In addition, the embodiments of the present application may further combine an electron microscope (Scanning Electron Microscope, SEM) and an energy dispersive spectrometer (EDS) to illustrate the capture capability of the composite isolation membrane of the present application on transition metal ions.

[0174] Figure 4 and Figure 5They are respectively a 3000 times magnified image of the negative electrode sheets of comparative example 1 and embodiment 1 of the present application after the self-discharge test under an electron microscope (Zeiss, SIGMA) and an energy distribution diagram of an energy spectrometer (X-max.EDS).

[0175] like Figure 5 As shown in the figure, after the negative electrode sheet in the electrochemical device of Example 1 of the present application passed the 1000h constant voltage test, the SEM magnified image showed no obvious transition metal deposition except the original negative electrode active material particles. In addition, the EDS spectrum also showed that there were no obvious transition metal peaks other than graphite on the negative electrode sheet in the electrochemical device of the present application. In contrast, Figure 4 As shown, after the negative electrode in the electrochemical device of Comparative Example 1 passed the constant voltage test for 1000 h, obvious transition metal deposition appeared in the magnified SEM image, and its EDS spectrum also showed that there was an obvious peak in the range of O atoms and Co metal, which represented the formation of metal oxide.

[0176] At the same time, ICP can be used to further make a quantitative comparison of the amount of transition metal deposition on the negative electrode plates of Comparative Example 1 and Example 1 of the present application. Figure 6 This is a diagram showing the amount of transition metal deposited on the negative electrode sheets of the lithium-ion batteries of Example 1 and Comparative Example 1 of the present application after the cycle test.

[0177] like Figure 6 As shown, the transition metal deposition concentration on the negative electrode sheet of Example 1 of the present application is only 1210ppm, while the transition metal deposition concentration on the negative electrode sheet of Comparative Example 1 can reach 5030ppm. It can be seen that the electrochemical device using the composite separator of the present application can effectively deposit transition metals on the negative electrode sheet, and reduce the impact of its deposition to 1 / 4 of the electrochemical device without the composite separator of the present application.

[0178] Through the comparison of the above embodiments and comparative examples, it can be clearly understood that the composite isolation membrane of the present application can effectively capture the transition metal ions dissolved from the positive electrode plate through the cation exchange layer, thereby reducing the deposition of transition metal ions on the negative electrode plate and the self-discharge rate of the lithium-ion battery, so that the electrochemical stability and cycle performance of the electrochemical device are improved to a certain extent, and the safety of the electrochemical device is also significantly improved.

[0179] References throughout the specification to "some embodiments", "partial embodiments", "one embodiment", "another example", "example", "specific example" or "partial example" mean that at least one embodiment or example in the present application includes the specific features, structures, materials or characteristics described in the embodiment or example. Therefore, descriptions appearing in various places throughout the specification, such as: "in some embodiments", "in an embodiment", "in one embodiment", "in another example", "in an example", "in a specific example" or "example", do not necessarily refer to the same embodiment or example in the present application. In addition, the specific features, structures, materials or characteristics herein may be combined in one or more embodiments or examples in any suitable manner.

[0180] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.

Claims

1. A composite isolation membrane, comprising: a first porous substrate; as well as A cation exchange layer, wherein the cation exchange layer comprises a second porous substrate grafted with a functional group, the functional group being selected from the group consisting of a sulfonic acid alkali metal group, a phosphate alkali metal group, and a combination thereof; The second porous substrate is selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, polyimide, ethylene-styrene copolymer, polysulfone, polyetheretherketone, polystyrene and combinations thereof. 2 . The composite barrier film according to claim 1 , further comprising a first coating layer, wherein the first coating layer comprises inorganic particles and a binder.

3. The composite isolation membrane according to claim 2 further comprises a second coating, wherein the second coating comprises a polymer binder, wherein the polymer binder is selected from the group consisting of copolymers of vinylidene fluoride and hexafluoropropylene, copolymers of vinylidene fluoride and trichloroethylene, polyacrylates, polyacrylic acid, polymethyl methacrylate, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene, polyhexafluoropropylene, copolymers of styrene and butadiene, and combinations thereof.

4. The composite isolation membrane according to claim 2, wherein: The first coating layer is disposed between the first porous substrate and the cation exchange layer.

5. The composite isolation membrane according to claim 3, wherein: The second coating layer is disposed between the first coating layer and the cation exchange layer.

6. The composite isolation membrane according to claim 2, wherein: The cation exchange layer is disposed between the first porous substrate and the first coating layer.

7. The composite isolation membrane according to claim 3, wherein: The second coating layer is disposed on the surface of the first coating layer.

8. The composite isolation membrane according to claim 1, wherein: The grafting concentration of the functional groups is 0.15 mmol / g to 0.95 mmol / g, and the thickness of the cation exchange layer is 0.5 μm to 10 μm.

9. A composite isolation membrane comprising: a first porous substrate; as well as A cation exchange layer, wherein the cation exchange layer comprises a polymer binder grafted with a functional group, wherein the functional group is selected from the group consisting of a sulfonic acid alkali metal group, a phosphate alkali metal group, and a combination thereof; The polymer binder is selected from the group consisting of vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-trichloroethylene copolymer, polyacrylate, polyacrylic acid, polymethyl methacrylate, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene, polyhexafluoropropylene, styrene-butadiene copolymer and combinations thereof. 10 . The composite separator according to claim 9 , further comprising a first coating layer, the first coating layer comprising inorganic particles and a binder, the first coating layer being disposed between the first porous substrate and the cation exchange layer.

11. The composite isolation membrane according to claim 9, wherein: The grafting concentration of the functional groups is 0.15 mmol / g to 0.95 mmol / g, and the thickness of the cation exchange layer is 0.5 μm to 10 μm.

12. An electrochemical device comprising: Positive electrode; Negative electrode; as well as The composite separator according to any one of claims 1 to 11, wherein the composite separator is disposed between the positive electrode sheet and the negative electrode sheet.

13. An electronic device comprising the electrochemical device according to claim 12.

Citation Information

Patent Citations

  • Composite porous isolating film and electrochemical device

    CN103904276A

  • Isolating membrane and electrochemical device

    CN108832061A